A Perception-based Study of Tribal Farmers Regarding Semi-intensive Mithun Rearing Systems in Nagaland, India - Narendra, V. N.; Banik, Trishita; Chamuah, J. K.; Somagond, Y. M.; Girish, P. S. (International Journal of Bio-resource and Stress Management, 2025)
The study was conducted between August and November, 2024 in four prominent Mithun-rearing districts of Nagaland-Phek, Peren, Kohima, and Kiphire. The objective of the study was to understand farmers’ perceptions of the semi-intensive Mithun rearing system and to analyze the relationship between their profile characteristics and perceptions. A total of 240 farmers from 16 villages were selected using a multi-stage sampling method. Data were collected through a structured questionnaire, and farmers’ perceptions were assessed on a five-point Likert scale. Findings revealed that the majority of farmers held a positive view of the semi-intensive system, acknowledging its benefits such as minimizing damage caused by Mithun to agricultural crops, providing better income, reducing calf mortality, enabling easier vaccination, offering better protection against predators, and improving herd management. Nevertheless, concerns were expressed about increased labour requirements and high initial infrastructure costs. Socio-economic and personal characteristics such as education, training, landholding size, innovativeness, extension contact, and livestock ownership significantly influenced perception levels. Among these, landholding, innovativeness, training, and extension contact together explained 81.4% of the variation in perception.The study concluded that the semi-intensive Mithun farming system had strong potential to enhance sustainable livestock production and improve the livelihoods of tribal farmers in Nagaland. With suitable policy interventions, capacity-building programs, and financial support, adoption of this system could be further strengthened to ensure both economic and ecological sustainability.